(3TQM GdgOGjI GdCKjQjIs - (3GdTjQGRj, GdbhGej, GdeqdG, UOQ GdOjf, eMeO Hf EHQGgje Hf jMji, J (B1059 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg eNJQY GdYbd GdaYGd hHYO ajbhd eMeO Hf EHQGgje GdTgjQ HGdUOQ GdTjQGRj deG JWGHbJ GdbhGfjf GdMcejI hGdCUhd GdOjfjI hdeG cKQ GdJeGS HYV GdeJQOOjf Edi GdeTJZdjf HbQGAI GdgOGjI ddMcje CKjQ GdOjf eaVd GdCHgQj Cf CcJH dgG TQMG s
(3BNQgG (B:s
(3Edi WHjYI GdLfS GdfGbUI GdJj HgG jJced hjJMUd ceGd GdLSe HGdGYJHGQ GdChd jchf ehVhhYG hHGdGYJHGQ GdKGfj jchf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5/303s
(3eYLe GdeDdajf (B3/31s
(3gOjI GdYGQajf (B2/279s
(3eYLe GdeWHhYGJ (B1174s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs